Analisis Penggunaan Aplikasi Coretax Dalam Pembuatan Faktur Pajak Pada PT Pindad - Siti Linda Mulyana (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to examine the use of the Coretax application in generating Tax Invoices at PT Pindad, the timing of Tax Invoice issuance to business partners, the obstacles encountered during the issuance process, and their impact on the companys tax administration. This study employed a qualitative method with a case study approach, and data were collected through interviews, observations, and documentation. The results show that PT Pindad began implementing the Coretax application in January 2025 as part of the Directorate General of Taxes digital tax administration system. The use of Coretax is considered more effective than the previous e-Faktur system because all tax administration processes have been integrated into a single platform. The Tax Invoice issuance process is carried out based on invoices from the Corporate Finance Department through stages of data input, verification, digital signature validation, and invoice printing. However, several technical obstacles were still identified, including system errors, the use of the Unit Financial Transaction Identification Number, and additional data requests from customers. These obstacles resulted in delays in data input and Tax Invoice issuance and affected the billing process to business partners. To address these issues, PT Pindad improved interdepartmental coordination and ensured data completeness to support smoother tax administration in accordance with applicable regulations.